ACCESSIBILITY IN HIGHER EDUCATION INVOLVES PEDAGOGICAL WORK AS WELL - Piza Candido, Eliane Aparecida [UNESP]; Siena do Nascimento, Claudia Regina [UNESP]; Agostini Martins, Morgana de Fatima (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2016)
This research presents a study on the inclusion in higher education and pedagogical practices that can contribute to the achievement of that inclusion, by pointing out the historic debt that Brazil has based on exclusion and segregation of people with disabilities who are in constant struggle for their rights, that being gradually secured have a greater focus on basic education and currently aims to involve more effectively to higher education. The qualitative research has used as a methodological procedure a bibliographical survey on the subject, as well as the check of national legal documents, which explain the Brazilian political commitments on constant struggle for achievement of educational inclusion and also social inclusion. The data showed that it is necessary to dismantle many obstacles, to combat prejudice and excluding measures that hinder access and permanence of these people in this teaching mode, because in their individuality, everyone has the right to obtain the necessary knowledge for their development. Thus, it was possible to notice that the professor finds himself as a fundamental pillar in the process of inclusion that requires preparation for practice teaching with sensitivity and excellence to identify the needs of each student and the best way to provide them with the desired and equal education.
Keywords: Inclusion; Higher education; Accessibility; Teacher-student